Role of the private sector in childbirth care: cross‐sectional survey evidence from 57 low‐ and middle‐income countries using Demographic and Health Surveys. Issue 12 (28th September 2015) - Benova, Lenka; Macleod, David; Footman, Katharine; Cavallaro, Francesca; Lynch, Caroline A.; Campbell, Oona M. R.
Abstract: Objective: Maternal mortality rates have decreased globally but remain off track for Millennium Development Goals. Good‐quality delivery care is one recognised strategy to address this gap. This study examines the role of the private (non‐public) sector in providing delivery care and compares the equity and quality of the sectors. Methods: The most recent Demographic and Health Survey (2000–2013) for 57 countries was used to analyse delivery care for most recent birth among >330 000 women. Wealth quintiles were used for equity analysis; skilled birth attendant (SBA) and Caesarean section rates served as proxies for quality of care in cross‐sectoral comparisons. Results: The proportion of women who used appropriate delivery care (non‐facility with a SBA or facility‐based births) varied across regions (49–84%), but wealth‐related inequalities were seen in both sectors in all regions. One‐fifth of all deliveries occurred in the private sector. Overall, 36% of deliveries with appropriate care occurred in the private sector, ranging from 9% to 46% across regions. The presence of a SBA was comparable between sectors (≥93%) in all regions. In every region, Caesarean section rate was higher in the private compared to public sector. The private sector provided between 13% (Latin America) and 66% (Asia) of Caesarean section deliveries. Conclusion: This study is the most comprehensive assessment to date of coverage, equity and quality indicators of delivery care by sector. The private sector provided a substantial proportion of delivery care in low‐ and middle‐income countries. Further research is necessary to better understand this heterogeneous group of providers and their potential to equitably increase the coverage of good‐quality intrapartum care.